EFEKTIVITAS PELAKSANAAN PROGRAM SIMPAN PINJAM PEREMPUAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - JULIARNI SIPAYUNG (Welfare StatE, 2013)
Development that implemented in rural areas still not involve the community, so there are still many rural development programs which are not in accordance with the needs of the community. The community just existence as object of the subject. To reduce Poverty that has been longer, the government has been established programs such as the National Program for Community Empowerment in Rural Areas. This research is to determine the effectiveness of women's savings and loans program the National Program for Community Empowerment in Rural Areas in the district Bangun Purba, regency Deli Serdang. Type of this research is descriptive that aims to illustrate about effectiveness of women's savings and loans program, the population of this research were 80 womens who get disbursement financial on 2011 in district Bangun Purba, regency Deli Serdang. Analysis technique using a single table which described quantitatively using a likert scale. Based on the analysis, it was concluded that the effectiveness of women's savings and loans national program for community empowerment program in rural areas in district Bangun Purba. is effective with the likert scale score 0,49. Indicator of program comprehension score is 0,45. Indicator of precision targeting score is 0,45. Indicator of time actually is 0,59. Indicator of goals reaching score is 0,48. Indicator of real charges of respondents emplymment is entrepreneur. Keywords: Effectiveness, Women's Savings and Loans Program, National Program Community Empowerment in Rural Areas